2015
DOI: 10.1039/c5ra14411f
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional MnO2/graphene hybrid as a binder-free supercapacitor electrode

Abstract: Highly aligned manganese dioxide (MnO 2 ) nanowall arrays electrodeposited onto Ti sheets are used as substrates to grow graphene (GR) through chemical vapor deposition (CVD), thus forming three-dimensional (3D) MnO 2 /GR hybrid composite.Furthermore, 3D MnO 2 /GR hybrid with different structures and properties has been prepared at different temperatures. The as-prepared hybrid materials could be directly used as supercapacitor electrodes without any binder and conductive additive, and fully maintain the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…226.9 F g -1 and 162.9 F g -1 at 1 A g -1 , 2 A g -1 , 5 A g -1 and 10 A g -1 , respectively, the values are comparable to the previous studies, as shown in Table 1 [27][28][29][30][31][32][33][34][35]. Our 4-µm thick MCG flexible films with a packing density of 0.87 g cm -3 , which leads to a significant gravimetric capacitance of 277.8 F cm -3 , which is much higher than previously reports.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
“…226.9 F g -1 and 162.9 F g -1 at 1 A g -1 , 2 A g -1 , 5 A g -1 and 10 A g -1 , respectively, the values are comparable to the previous studies, as shown in Table 1 [27][28][29][30][31][32][33][34][35]. Our 4-µm thick MCG flexible films with a packing density of 0.87 g cm -3 , which leads to a significant gravimetric capacitance of 277.8 F cm -3 , which is much higher than previously reports.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
“…These authors practiced this scheme in later work altering the silicone matrix employed 5 . The grafting of dipole of N ‐allyl‐ N ‐methyl‐ p ‐nitro aniline to two silicone polymers commercially used (Sylgard 184 from Dow corning and elastosil RT 625 from Wacker) in the concentration range from 0 to 10.7 wt% enhanced the dielectric permittivity from ε = 2.84 to ε = 6.5 for sylgard 184 and from ε = 3.17 to ε = 5.57 for elastosil RT 625 69 and reduced the Young's modulus for sylgard 184 from Y = 2490 to 850 kPa and for elastosil RT 625 from Y = 303 to Y = 142 kPa 69 . The samples with greater dipole behavior values in both silicones demonstrated increased electromechanical efficiency compared to ordinary silicones, although in both cases breakdown value decreased.…”
Section: Ways To Improve the Actuation Efficiency Of Dea Devicesmentioning
confidence: 99%
“…Carbon based nanomaterials possess lots of advanced properties, including high specic surface area, abound electrochemically active sites, light weight and high electronic conductivity, and were deemed as the most perfect supplementary materials for birnessite based electrode structures. 73,90 Three main kinds of carbon materials, including graphene, [91][92][93][94][95] carbon nanotubes [96][97][98][99][100][101] and porous carbon, [102][103][104] are widely investigated in view of their good electrical conductivity and excellent mechanical/electrochemical stability.…”
Section: Enhancing Conductivitymentioning
confidence: 99%